How carbon taxes and subsidies affect the implementation of low-carbon housing? An evolutionary game theory analysis - Lv, Wenwen; Li, Jun (Frontiers in Environmental Science, 2025)
IntroductionSubsidy policies and carbon tax policies are effective means of encouraging the development of low-carbon residential buildings. However, how to utilize these two policy tools of carbon tax and subsidies to more efficiently incentivize the development of low-carbon residential buildings remains a topic worthy of further exploration. This paper explores the mechanisms by which carbon tax and subsidies incentivize the implementation of low-carbon residential buildings and clarifies the boundary conditions for the effectiveness of these two policy tools.MethodsWe built a stochastic evolutionary game that couples three agent groups—government, real-estate developers, and homebuyers—and explicitly incorporates policy shocks (carbon tax vs. subsidy) and environmental noise. A series of Monte-Carlo simulations was run to trace the share of low-carbon developers and buyers over time; critical thresholds and noise boundaries separating qualitatively different regimes were identified with bifurcation analysis.Results and discussionThe evolutionary process of low-carbon housing development, whether under a carbon tax policy or a low-carbon subsidy policy, includes three stages: (1) the initial stage, where relying solely on government subsidies or carbon taxes is insufficient to effectively implement low-carbon housing under various noise intensities; (2) the development stage, where as the proportions of real estate developers adopting low-carbon strategies and homebuyers purchasing low-carbon housing increase, a chaotic relationship emerges between the implementation of carbon taxes, subsidies, and low-carbon housing under certain noise intensities; and (3) the stable stage, where low-carbon housing can be successfully implemented and a qualitative leap is achieved when a certain threshold proportion of real estate developers and homebuyers adopt low-carbon strategies.